Extraction and Electrophoresis of DNA from the Remains of Mexican Ancient Populations - Muñoz, Maria de Lourdes; Lopez-Armenta, Mauro; Moreno-Galeana, Miguel; Díaz-Badillo, Alvaro; Pérez-Ramirez, Gerardo; Herrera-Salazar, Alma; Mejia-Pérez-Campos, Elizabeth; Gómez-Chávez, Sergio; Martínez-Meza, Adrián (IntechOpen, 2012)
None